Discontinuous Finite Element Method for Convection-Diffusion Equations (Journal of Computational Mathematics, 2021)
A discontinuous finite element method for convection-diffusion equations is proposed and analyzed. This scheme is designed to produce an approximate solution which is completely discontinuous. Optimal order of convergence is obtained for model problem. This is the same convergence rate known for the classical methods.